FIRM CHARACTERISTICS AND FINANCIAL REPORTING QUALITY OF LISTED CONSUMABLE GOODS COMPANIES IN NIGERIA (Journal of Contemporary Issues in Accounting, 2021)
This study examined the influence of firm characteristics on the financial reporting quality of listed consumable goods companies in Nigeria from 2014 to 2019. The objective of this paper was to examine the link between firm characteristics like firm size, leverage, board composition, institutional shareholding, profitability, and liquidity and financial reporting quality of listed consumable goods companies in Nigeria. This study adopted a longitudinal panel research design. Data were sourced from annual financial reports of 13 selected consumable goods companies in Nigeria from 2014 to 2019. This study used panel least square regression analysis. The results revealed that the institutional shareholding, board composition, and liquidity influenced financial reporting quality positively and significantly. The firm size influences financial reporting quality negatively but significantly; while leverage and profitability were positive but had an insignificant influence on the quality of financial reporting.
Keywords: Financial reporting quality; Board composition; Profitability; Institutional shareholding; Liquidity